Magnetic properties of γ-Fe 2O 3/poly(ether- ester) nanocomposites - Guskos, N.; V. Likodimos; Glenis, S.; Maryniak, M.; Baran, M.; Szymczak, R.; Roslaniec, Z.; Kwiatkowska, M.; Petridis, D. (Journal of Nanoscience and Nanotechnology, 2008)
The magnetic properties of γ-Fe 2O 3 nanoparticles embedded in a thermoplastic elastomer poly(ether-ester) copolymer by the in situ polycondensation reaction process have been investigated by means of magnetization and ferromagnetic resonance (FMR) measurements at low filler concentrations of 0.1 and 0.3 wt% with the magnetic additive introduced in the polymer matrix in powder and solution form. The magnetic behavior of the magnetopolymeric nanocomposites indicates significant interparticle interaction effects that depend mainly on the dispersion state of the magnetic nanoparticles as well as their concentration, consistent with the variation of the particle microstructure characterized by magnetic aggregates in the nanometer and micron scale for the solution and powder dispersions, respectively. The magnetization and FMR results at different filler concentrations and dispersions show a close correspondence to the relaxation processes of the copolymer, implying the coupling of polymeric and magnetic properties. Copyright © 2008 American Scientific Publishers All rights reserved.